EXPERIÊNCIAS FORMACIONAIS EM/NA REDE - Carvalho , Felipe; Marcos Vinícius Dias de Menezes; Edméa Santos; Mariano Pimentel; Tania Lucía Maddalena; Wallace Carriço de Almeida (Revista Docência e Cibercultura, 2024)
v. 8 n. 2 (2024): Publicação contínua – Jan./Dez.